Sanksi Pidana terhadap Siswa yang Melakukan Tindak Pidana Penganiayaan Kepada Guru - Komang Devi Triveni; A.A. Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2021)
The education is the main thing that will sustain the progress of a nation. Teachers are professionals who have the task of teaching, educating and training. The teacher's job is to teach students to have the knowledge and skills of each subject area. In carrying out their obligations, teachers are protected by Article 39 Paragraph (1) of Law Number 14 of 2005 concerning Teachers and Lecturers and strengthened by the issuance of Government Regulation Number 74 of 2008. In practice, Teachers often receive unpleasant treatment such as persecution by students until causing the death of the teacher and the criminal sanction that can be imposed on the student refers to Article 338 concerning Murder where persecution deliberately takes the life of another person. This study aims to explain the management of criminal acts of molestation committed by students to teachers and to explain the criminal sanctions for students who commit acts of molestation to the teacher. This research uses normative legal methods and analysis of legal interpretation and exposure, because this is related to the outcome of criminal sanctions, the approach used is the statutory approach. The data sources used were prime and secondary legal data. The results showed that in the Criminal Code Chapter XX concerning persecution, this is useful to provide a deterrent effect on the students themselves. The Criminal Code for criminal sanctions against the perpetrator refers to Article 338 of the Criminal Code regarding murder, considering that the perpetrator is still a minor, the maximum sentence given to the perpetrator (one half) of the maximum imprisonment for adults as regulated in Law Number 11 of 2012 concerning the Juvenile Justice System.